PERAN DAN KOMPETENSI GURU DALAM E-LEARNING - Endang Nugraheni (LPPM Universitas Terbuka, 2009)
E-learning has been growing rapidly despite its pros and cons. Good e-learning is based on principles and pedagogy similar to other type of leaming. Align with the shift of educafional paradigm from teacher-centered to student-centered, sooner or later teachers should adapt themselves to the new roles. This article discusses teachers' roles and competencies related to e-learning.